2001
DOI: 10.1164/ajrccm.164.10.2104061
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants and Asthma in Adults

Abstract: A protective role for dietary antioxidants in asthma has been proposed. However, epidemiological evidence to implicate antioxidant vitamins is weak, and data on the role of flavonoid-rich foods and antioxidant trace elements are lacking. We carried out a population-based case-control study in South London, UK, to investigate whether asthma is less common and less severe in adults who consume more dietary antioxidants. Participants were aged 16-50 yr and registered with 40 general practices. Asthma was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(70 citation statements)
references
References 48 publications
2
67
0
1
Order By: Relevance
“…In our sample, however, no effects of antioxidant (vitamins C, E, A, b-carotene) intake or of the consumption of antioxidant-providing food groups such as fruit (eg apples) intake, as potential dietary source of flavonoids, or meat intake, as potential source for selenium on asthma risk, were observed. This is consistent with observations of Woods et al (2003), whereas Shaheen et al (2001) observed an inverse association between apple consumption and selenium intake and asthma.…”
Section: Discussionsupporting
confidence: 92%
“…In our sample, however, no effects of antioxidant (vitamins C, E, A, b-carotene) intake or of the consumption of antioxidant-providing food groups such as fruit (eg apples) intake, as potential dietary source of flavonoids, or meat intake, as potential source for selenium on asthma risk, were observed. This is consistent with observations of Woods et al (2003), whereas Shaheen et al (2001) observed an inverse association between apple consumption and selenium intake and asthma.…”
Section: Discussionsupporting
confidence: 92%
“…Whether the worldwide increase in the prevalence of allergic diseases is directly associated with diet is unknown, but a recently reported population-based case-control study found that consumption of apples or red wine was negatively associated with asthma prevalence or severity, respectively, possibly due to the protective effect of flavonoids [24]. In addition, a cohort study in Finland demonstrated a lower asthma incidence for higher total flavonoid intakes (relative risk = 0.65, p = 0.04), mainly in the form of apples and oranges [25].…”
Section: Discussionmentioning
confidence: 99%
“…58 With regard to asthma, a protective relationship was found between dietary Se intake and asthma in adults in a large population-based case-control study in London (OR 0.84 per quintile increase; 95% CI 0.75-0.94; P = 0.002). 59 In a small nested case-control study, current wheeze among New Zealand children was found to be more common in those with low levels of Se in serum samples collected eight-years previously (OR 3.1; 95% CI 0.9-11.8). 60 Another small study in intrinsic asthmatics showed significant clinical improvement upon supplementation with Se at 100mcg/d as sodium selenite.…”
Section: Thyroid Functionmentioning
confidence: 99%